Conceptual analysis of causation and theoretical utility in everyday contexts - Weber, Erik; De Vreese, Leen (Logique et Analyse, 2009)
In this paper we elaborate Ned Hall's theoretical utility perspective for causation in everyday contexts. We do this by presenting some instances of it, thereby adding some flesh to the skeleton that Hall has provided. Our elaboration of the theoretical utility perspective also provides arguments for it: the instances we present show the fruitfulness of the approach. A question raised by Hall's proposal is: should we give up descriptive analysis of causation (and descriptive analysis in general) completely? We argue that, at least for causation, traditional descriptive conceptual analysis must be given up. However, we also argue that a more modest variant of descriptive conceptual analysis can be useful.